Rancang Bangun Aplikasi Berbasis Mobile Untuk Digitalisasi Layanan Jasa Jahit - Kustoyo, Yoyo; Asriningtias, Yuli (SAFE-Network, 2025)
Expanding service offerings using apps has become a crucial strategy for MSMEs as consumer behavior shifts toward fast, easy, and efficient services. This study focuses on the operational conditions of tailors, who still rely on direct ordering, manual recording, and local reach, resulting in long queues, administrative errors, and limitations in business development. Referring to the literature on MSME digital transformation, this study proposes the development of a mobile sewing service application to improve operational efficiency, service quality, and market access. The application is designed with features such as remote ordering, design reference upload, cost and time estimation, order status tracking, automatic notifications, and structured digital recording for demand analysis. Evaluation includes usability testing, measurement of processing time and administrative error rates, and a customer satisfaction survey. Implementation of the application is expected to reduce the need for physical presence, improve service accuracy and transparency, and expand market reach, with digital readiness and interface design as key success factors.